Evaluating the Efficacy and Environmental Impact of Green Solvents in Organic Synthesis: A Systematic Review - Fatima Aboushabour; Salwa Rahil (AlQalam Journal of Medical and Applied Sciences, 2025)
These solvents which are known as green or eco-friendly. where used as alternatives to traditional organic solvents, designed to have little or no harmful effects on human health and the environment. its inception roots from renewable sources. These solvents such as water, ethanol, ethyl lactate, and ionic liquids. these types of solvents have become commonly used in all fields, and play an important role in pharmaceuticals and industrial cleaning, and organic synthesis. Using such solvents contributes to low cost, reduced energy consumption, and lower environmental.